Regulasi Diri dengan Kecemasan Menghadapi Dunia Kerja pada Mahasiswa Tingkat Akhir di Universitas X - Putri Wulandari; Th. Dewi Setyorini; Femmy Lekahena (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Final year students feel anxious in facing the world of work, because they feel that finding a job is increasingly difficult and their personal qualities are inadequate. Therefore, efforts are needed to prevent or reduce this anxiety, one of which is through self-regulation. This study aims to determine the relationship between self-regulation and anxiety in facing the world of work in final year students at the University of Proclamation 45 Yogyakarta. This study used a quantitative research method. The subjects in this study were 90 final year students with a sampling technique of simple random sampling. The measuring instruments used in this study were the Self-Regulation Scale (25 items α = 0.881) and the Anxiety Scale in Facing the World of Work (22 items α = 0.88) which have been tried out on 75 final year students. Using the Pearson Product Moment correlation test, a correlation coefficient of -0.493 was found with a significance of 0.000 (p <0.01). These results indicate that there is a significant negative relationship between self-regulation and anxiety in facing the world of work.